The interbranchial lymphoid tissue of Atlantic Salmon (Salmo salar L) extends as a diffuse mucosal lymphoid tissue throughout the trailing edge of the gill filament. (September 2015) - Dalum, Alf S.; Austbø, Lars; Bjørgen, Håvard; Skjødt, Karsten; Hordvik, Ivar; Hansen, Tom; Fjelldal, Per G.; Press, Charles McL; Griffiths, David J.; Koppang, Erling O.
ABSTRACT Cover illustration. The teleost gill forms an extensive, semipermeable barrier that must tolerate intimate contact with the surrounding environment and be able to protect the body from external pathogens. The recent discovery of the interbranchial lymphoid tissue has initiated an anatomical and functional investigation of the lymphoid tissue of the salmonid gill. In this issue of the Journal of Morphology, Dalum et al. (pp. 1075–1088) report about the novel interbranchial lymphoid tissue of Atlantic salmon. The cover image shows the interbranchial lymphoid tissue with its distal distribution in a gill filament presented with immune‐labelled T cells. It represents an evolutionary structure unparalleled by any other known vertebrate lymphoid tissue.